Organizing participation of a lifestyle sport: The constitutive power of new media discourse. (March 2020) - 'Roth' Smith, William
Abstract: The participants of action, extreme, or lifestyle sports, such as skateboarding and BMX biking, have a lengthy history of producing, consuming, and sharing new media content. This study explores how communication, particularly through new media discourse, enables the organizing process that sustains lifestyle sport participation. Lifestyle sport participants without access to public practice areas often voluntarily construct their own organic participation spaces. After observations, interviews, and social media discourse analysis conducted within a loose collective of BMX dirt jump bikers, findings reveal that the discursive themes of informatives and acknowledgements generate the overall feeling of stoke—an intense excitement and energy surrounding participation in the sport . Stoke, in turn, motivates individuals to contribute and participate in the shared space, while directives then regulate the contributions encouraged through stoke . Thus, discourse plays a role in organizing the participants of a loose collective into a more recognizable assemblage. The article contributes to communication constitutes organizing (CCO) theoretical perspectives by providing further empirical evidence of the hybrid agency of attitudes, and by theorizing discourse as a powerful force for organizing lifestyle sport participation.